Analyses of merlin/NF2 connection to FAK inhibitor responsiveness in serous ovarian cancer - Shah, Nina R. (2014)
OBJECTIVE: Focal adhesion kinase (FAK) is overexpressed in serous ovarian cancer. Loss of merlin, a product of the neurofibromatosis 2 tumor suppressor gene, is being evaluated as a biomarker for FAK inhibitor sensitivity in mesothelioma. Connections between merlin and FAK in ovarian cancer remain undefined. METHODS: Nine human and two murine ovarian cancer cell lines were analyzed for growth in the presence of a small molecule FAK inhibitor (PF-271, 0.1 to 1 μM) for 72 h. Merlin was evaluated by immunoblotting and immunostaining of a human ovarian tumor tissue array. Growth of cells was analyzed in an orthotopic tumor model and evaluated in vitro after stable shRNA-mediated merlin knockdown. RESULTS: Greater than 50% inhibition of OVCAR8, HEY and ID8-IP ovarian carcinoma cell growth occurred with 0.1 μM PF-271 in anchorage-independent (p<0.001) but not in adherent culture conditions. PF-271-mediated reduction in FAK Y397 phosphorylation occurred independently of growth inhibition. Suspended growth of OVCAR3, OVCAR10, IGROV1, IGROV1-IP, SKOV3, SKOV3-IP, A2780, and 5009-MOVCAR was not affected by 0.1 μM PF-271. Merlin expression did not correlate with serous ovarian tumor grade or stage. PF-271 (30 mg/kg, BID) did not inhibit 5009-MOVCAR tumor growth and merlin knockdown in SKOV3-IP and OVCAR10 cells did not alter suspended cell growth upon PF-271 addition. CONCLUSIONS: Differential responsiveness to FAK inhibitor treatment were observed. Intrinsic low merlin protein levels correlated with PF-271-mediated anchorage-independent growth inhibition, but reduction in merlin expression did not induce sensitivity to FAK inhibition. Merlin levels may be useful for patient stratification in FAK inhibitor trials.